Quality of Health Services in The Intra-Hospital Patient Transfer Process - Aulia, Zalsa; Suyatno, Suyatno (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyse the quality of health services in the intra-hospital patient transfer process at RSUD Limpung based on the theory of Zeithaml, Parasuraman, and Berry (tangibles, reliability, responsiveness, assurance, empathy). The background of the study was based on the obstacles in the delay of operation registration, limited human resources in the Central Surgical Installation, and poor communication between units in the process of intra-hospital patient transfer. The method used was descriptive qualitative with purposive sampling technique, involving the doctor in charge, emergency room nurse, head of the room, administrative officer, and family of BPJS PBI and non-PBI patients. Data were collected through observation, in-depth interviews, and documentation, then analysed through reduction, presentation, and conclusion drawing. The results showed that patient transfer services at RSUD Limpung were considered good in the aspects of responsiveness, assurance, and empathy, but there were still obstacles in tangibles and reliability, with the novelty of this research lies in the focus of the study of the intra-hospital patient transfer process, especially BPJS patients (PBI and non-PBI), which is still rarely studied. So it is necessary to strengthen coordination between units to ensure more efficient and effective service quality